Effects of oil palm (Elaeis guineensis) fruit extracts on insulin secretion from BRIN BD11 cells - Sharif, Faez; Hamid, Muhajir; Ismail, Amin; Adam, Zainah (Nutrition Society of Malaysia, 2015)
Diabetes has been one of the top ten causes of death in Malaysia. Recently, the oil palm Elaeis guineensis has been explored in several antidiabetic studies. Nevertheless, the oil palm fruit has never been investigated for its antidiabetic effect. Therefore, this study was conducted to evaluate the antidiabetic properties of oil palm fruit which specifically focusing on its effects in stimulating insulin secretion from pancreatic ß cell. The insulinotropic activity of oil palm fruit aqueous extract (OPF) on clonal pancreatic ß cell line was investigated using BRIN BD11 cell line. The cell lines were incubated with different concentrations of OPF to evaluate the stimulatory effect of OPF toward insulin secretion from BRIN BD11 cells using the Rat Insulin ELISA Assay Kits. OPF (100-1000µg/ml) were shown to significantly induce insulin secretion by a multiple of 1.97-2.58 in the BRIN BD11 cells. The highest insulin secretion increase (2.58-fold, p<0.001) was induced by 500 µg/ml in the OPF treated group. Evaluation of the possible mechanisms involved suggested that the mechanisms of insulin secreting activity of the 500 µg/ml OPF extract may involve the K+ATP channel-dependent pathway which exerts an insulin secretion effect through depolarizing the membrane of pancreatic-ß cells. The present study has revealed the presence of insulinotropic activity in Elaeis guineensis fruit. Future work assessing its use as a source of active components may provide new opportunities for the treatment of diabetes which are safe, efficient and exert a lesser amount of side effects.